Teacher’s Perspectives on the Role of Inclusive Education in Fostering the Social and Emotional Well-being of Students with Special Educational Needs - Aslam, Aiman; Manzoor, Dr. Afaf; Sajjad , Rimsha (ACADEMIA International Journal for Social Sciences, 2025)
This paper reviewed the perceptions of teachers on the significance of inclusive education in promoting the social and emotional well-being of students with special educational needs (SEN) in general school institutions. It was quantitative descriptive research design; a self-constructed Likert-scale questionnaire was used where 100 teachers were chosen through convenience sampling with the help of an online survey. The perceptions of teachers were summarized using descriptive statistics and the independent samples t-tests and one-way ANOVA were used to determine differences in training, teaching experience, professional role, and grade levels. The results showed that teachers positively thought that inclusive education may help foster the aspects of acceptance, confidence, and positive peer relationships among SEN students, yet they also mentioned significant issues that were associated with large class groups, lack of time, insufficient resources, and ineffective cooperation with specialists. The teachers who were specially trained in inclusive education showed better perceptions and confidence as compared to the teachers who were untrained and there was a wide difference among roles and levels of experience. The paper finds that, although inclusive education has a high potential to improve the social and emotional wellbeing of SEN students, this would require long term professional development, better resource distribution to them and increased support mechanism in the schools.